Kinetics and Mechanism of Mn(II) Catalyzed Periodate Oxidation of 4-Chloro-2-methylaniline - Kaushik, R.D.; Devi, Sumitra; Shashi,; Amrita, (Asian Journal of Chemistry, 2016)
Kinetic-mechanistic studies made for periodateoxidation of 4-chloro-2-methylaniline (CMA) in acetone-water medium have been used for derivation of rate law and proposing mechanism which satisfy various observations like first order in each reactant and catalyst stoichiometry (1 mol CMA : 2 mol periodate), kinetic parameters, main product identified (5-chloro-2-methyl-1,2-benzoquinone) and the effect of pH, dielectric constant, and ionic strength on reaction rate.